Method Development and Quantitative Elemental Analysis of Mentha Longifolia L. Leaves from Saudi Arabia by Total Reflection X-Ray Fluorescence. (13th June 2018) - Shaltout, Abdallah A.; Abdel-Hameed, El-Sayed S.; Salman, Mahmoud; Kregsamer, Peter; Wobrauschek, Peter; Streli, Christina
ABSTRACT: A method has been developed for the quantitative elemental analysis of Mentha longifolia L. leaves collected from different cities in Saudi Arabia using total reflection X-ray fluorescence. Using a microwave digestion system, 100 mg of each sample was completely digested using 3 mL of nitric acid and 2 mL of hydrogen peroxide. The stabilization of the digested samples on the silicon reflectors was studied using a silicone solution and polyvinyl alcohol. 5 µL of either silicone solution or polyvinyl alcohol (1% m/v) was pipetted and dried on the silicon reflector prior to the deposition of the digested samples. It was recognized that there is some enhancement on the intensity of the peak area with the silicone solution at photon energies less than 11 keV. However, the obtained results confirm the ability of using silicone solution or polyvinyl alcohol (1% m/v) as the stabilizer prior to the deposition of the sample droplet on the quartz reflector. However, the silicone solution was more applicable. Based on the developed method, 15 elements were quantified, namely, P, S, Cl, K, Ca, Ti, Cr, Mn, Fe, Cu, Zn, Br, Rb, Sr, and Ba. Based on the present quantitative analysis results, M. longifolia samples collected from Al-Madina city had the highest concentration of P, Cl, K, Ti, Fe, Ni, and Cu. The lowest concentrations of P, S, Cl, K, Mn, Ni, and Br were found in Taif-Shafa.